RANCANG BANGUN ALAT UKUR KADAR GULA DALAM DARAH NON INVASIVE MENGGUNAKAN ESP32 DAN BLYNK: DESIGN A NON-INVASIVE BLOOD SUGAR MEASUREMENT USING ESP32 AND BLYNK - Vadel Amanika; Sunanto S.Kom,M.Kom (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2024)
The compatibility of ESP32 microcontrollers in Internet of Things (IoT) implementations covers almost all fields. Has the potential to monitor blood sugar levels non-invasively with the presence of Fotodioda Sensors and Infared LED lights and fingers as measurement objects without the need to injure patients or invasively in the aim to improve public health services, especially in an effort to prevent diabetes mellitus. ESP32 microcontroller also has compatibility in the use of Blynk which can be used to be a medium to monitor blood sugar levels and can be displayed on a computer monitor or smartphone by opening Blynk private, also with the utilization of Light intensity using fotodioda sensors and LED lights will be designed Non-Invasive Blood Sugar Measuring Instruments Using Prototyping Methods by utilizing ESP32 and Blynk and conducted experiments to see performance and comparison of accuracy with Glucometers in general and utilization in applications in the Health sector. In the prototype experiment of the Blood Glucose Measurement Device, the light absorption calculation produced by the combination of photodiode sensors and LED lamps can be utilized for measuring blood glucose levels without the need for direct blood sampling from the user. The implementation is straightforward and includes a monitoring system using Blynk, facilitating the process of blood glucose monitoring via both smartphones and users' computers. The overall accuracy result of the non-invasive blood glucose measurement device prototype reached 95% based on multiple conducted experiments.